Plan estratégico de desarrollo de turismo rural sostenible para el municipio de Coello 2025-2027 (2025)
This research develops a Strategic Plan for Sustainable Rural Tourism Development in the municipality of Coello 2025–2027, aimed at diversifying the local economy, creating community opportunities, and promoting environmental and cultural preservation. The study begins with a market diagnosis and SWOT analysis, identifying strengths such as natural wealth, cultural heritage, and strategic location, along with weaknesses related to the lack of tourism infrastructure and community training. It also highlights opportunities in the global trend towards sustainable tourism and threats linked to regional competition and environmental impact. The methodology combines direct observation, surveys, quantitative analysis, and community participation, leading to a strategic framework focused on sustainability, inclusion, and competitiveness. The plan proposes key action lines in training, promotion, infrastructure development, strengthening of tourism services, and institutional coordination. It includes training programs, digital promotion campaigns, public-private partnerships, and environmental monitoring mechanisms. In conclusion, the document provides a 2025–2027 roadmap that positions sustainable rural tourism as a driver of local development, enhancing community well-being in Coello and consolidating the municipality as a distinctive and responsible destination.